2017
DOI: 10.1038/srep45601
|View full text |Cite
|
Sign up to set email alerts
|

Development of a multiplex loop-mediated isothermal amplification method for the simultaneous detection of Salmonella spp. and Vibrio parahaemolyticus

Abstract: Rapid detection of food-borne pathogens is important in the food industry, to monitor and prevent the spread of these pathogens through contaminated food products. We therefore established a multiplex real-time loop-mediated isothermal amplification (LAMP) assay to simultaneously detect and distinguish Salmonella spp. and Vibrio parahaemolyticus DNA in a single reaction. Two target sequences, one specific for Salmonella and the other specific for Vibrio parahaemolyticus, were amplified by specific LAMP primers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 29 publications
2
44
0
Order By: Relevance
“…This indicated Bst 3.0 could be a useful model for studying non-specific amplification. We observed that early amplifying products corresponded to specific amplification events, and the later products corresponded to non-specific amplification, supporting our prediction that we could use T m as a proxy for sequence identity, as is common with PCR and has been used previously in LAMP (25)(26)(27)(28)(29).…”
Section: Bulk Lamp Studies Reveal Non-specific Products With High Melsupporting
confidence: 86%
“…This indicated Bst 3.0 could be a useful model for studying non-specific amplification. We observed that early amplifying products corresponded to specific amplification events, and the later products corresponded to non-specific amplification, supporting our prediction that we could use T m as a proxy for sequence identity, as is common with PCR and has been used previously in LAMP (25)(26)(27)(28)(29).…”
Section: Bulk Lamp Studies Reveal Non-specific Products With High Melsupporting
confidence: 86%
“…2b). Similar melt curve-based real-time LAMP analysis was reported for clinical pathogens like Salmonella and Vibrio (Liu et al 2017), Arcanobacterium pluranimalium (Abdulmawjood et al 2015) and Herpes virus (Chen et al 2013). The melting curve analysis was used for species level genotyping of pathogenic Leptospira by targeting variable-number tandem repeats (Naze et al 2015).…”
Section: Development Of Realampsupporting
confidence: 68%
“…Similar melt curve‐based real‐time LAMP analysis was reported for clinical pathogens like Salmonella and Vibrio (Liu et al . ), Arcanobacterium pluranimalium (Abdulmawjood et al . ) and Herpes virus (Chen et al .…”
Section: Resultsmentioning
confidence: 99%
“…17,31 LAMP has the capacity for incorporation into assays for medical investigation, genetic testing, environmental testing and rapid testing of food products, especially in resource-constrained environments. 17 LAMP has found application in detecting resistance genes such as bla KPC and bla NDM-1 in E. coli, Klebsiella pneumonia and Acinetobacter baumannii 32 as well as identification of bacteria like E. coli, 33 Mycobacteria, 34 Vibrio parahemolyticus, Salmonella spp 35 and A. baumannii. 36 LAMP with a detection limit of 1ng has also been successfully used for rapid detection of Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans, both of which cause periodontitis in humans.…”
Section: Loop-mediated Isothermal Amplification (Lamp)mentioning
confidence: 99%